A «necklace» of large clusters of strategic raw materials over a stagnant oceanic slab in East Asia - Natalia Boriskina (AIMS Geosciences)
An analysis of geological-geophysical, metallogenic, geochronological, and seismic tomographic studies in territories joining Southeast Russia, East Mongolia, and Northeast China led to the conclusion that deep geodynamics significantly influenced the formation of highly productive ore-magmatic systems in the Late Jurassic-Early Cretaceous. This influence was likely manifested through the initiation of decompression processes around stagnant slab boundaries in the Late Mesozoic. Decompression and advection, which are particularly active near the natural boundaries of the slab, act as triggers for the intense interaction of under and over subduction asthenospheric fluids with adjacent sections of the mantle and for the directed upwelling of powerful flows of matter and energy into the lithosphere. These flows determine the locations of intermediate and peripheral magma chambers: Primary chambers in the lower lithosphere among the metasomatized mantle and lower crust and associated chambers in the middle and upper cratonized parts of the lithosphere. Large ore clusters containing noble metals (Au, PGE), uranium, fluorite, and Cu-Mo-porphyry deposits are associated with late- and postmagmatic derivatives of the emerging magma chambers over the frontal and peripheral (paleotransform) boundaries of a stagnant Pacific slab. These large Late Mesozoic ore clusters and districts form a distinctive 'necklace' of strategic materials in East Asia.